Design and Fabrication of Hierarchical NiCoP–MOF Heterostructure with Enhanced Pseudocapacitive Properties. Issue 21 (16th April 2021) - He, Shixue; Guo, Fengjiao; Yang, Qi; Mi, Hongyu; Li, Jingde; Yang, Nianjun; Qiu, Jieshan
Abstract: Metal–organic framework (MOF)‐derived heterostructures possessing the merits of each component are thought to display the enhanced energy storage performance due to their synergistic effect. Herein, a functional heterostructure (NiCoP–MOF) composed of nickel/cobalt‐MOF (NiCo–MOF) and phosphide (NiCoP) is designed and fabricated via the localized phosphorization of unusual lamellar brick‐stacked NiCo–MOF assemblies obtained by a hydrothermal method. The experimental and computational analyses reveal that such‐fabricated heterostructures possess the modulated electronic structure, abundant active sites, and hybrid crystalline feature, which is kinetically beneficial for fast electron/ion transport to enhance the charge storage capability. Examined as the supercapacitor electrode, the obtained NiCoP–MOF compared to the NiCo–MOF delivers a high capacity of 728 C g −1 (1.82 C cm −2 ) at 1 A g −1 with a high capacity retention of 430 C g −1 (1.08 C cm −2 ) when increasing the current density to 20 A g −1 . Importantly, the assembled solid‐state NiCoP–MOF‐based hybrid supercapacitor displays superior properties regarding the capacity (226.3 C g −1 ), energy density (50.3 Wh kg −1 ), and durability (≈100% capacity retention over 10 000 cycles). This in situ heterogenization approach sheds light on the electronic structure modulation while maintaining the well‐defined porosity and morphology, holding promise for designing MOF‐based derivatives for high performance energy storage devices. Abstract : A novel hierarchical heterostructure combining the merits of nickel/cobalt–organic framework and phosphide is fabricated via the localized phosphorization. Benefitting from the improved conductivity and increased active sites, this hetero‐material displays high charge storage capability. The assembled solid‐state device exhibits a high energy density of 50.3 Wh kg −1 and excellent durability.